2012
DOI: 10.1186/1472-6920-12-112
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of student preparedness for clinical learning: clinical educator perspectives using the Delphi approach

Abstract: BackgroundDuring clinical placements, clinical educators facilitate student learning. Previous research has defined the skills, attitudes and practices that pertain to an ideal clinical educator. However, less attention has been paid to the role of student readiness in terms of foundational knowledge and attitudes at the commencement of practice education. Therefore, the aim of this study was to ascertain clinical educators’ views on the characteristics that they perceive demonstrate that a student is well pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 24 publications
9
94
0
Order By: Relevance
“…These findings are supported by those of a recent large online Delphi study, conducted in Australia, exploring clinical educators' perspectives on students' preparedness for practice-based learning in occupational therapy, physiotherapy and speech and language therapy. This research identified among other things, the importance of students' willingness to actively engage by being curious and asking questions, responding to requested tasks, being enthusiastic and taking responsibility for their own learning (Chipchase et al 2012). Developing these ideas further, this paper aims to theorise and promote understanding of how such student engagement motivates practice educators and energizes the student-educator relationship.…”
Section: Student-educator Relationshipsmentioning
confidence: 99%
“…These findings are supported by those of a recent large online Delphi study, conducted in Australia, exploring clinical educators' perspectives on students' preparedness for practice-based learning in occupational therapy, physiotherapy and speech and language therapy. This research identified among other things, the importance of students' willingness to actively engage by being curious and asking questions, responding to requested tasks, being enthusiastic and taking responsibility for their own learning (Chipchase et al 2012). Developing these ideas further, this paper aims to theorise and promote understanding of how such student engagement motivates practice educators and energizes the student-educator relationship.…”
Section: Student-educator Relationshipsmentioning
confidence: 99%
“…Jensen and Daniel (2010) noted that fieldwork educators were more hesitant to accept level II fieldwork students due to concerns about the unprofessional behaviors of students. Chipchase et al (2012) In separate studies, Gutman et al (1998) as well as James and Musselman (2006) determined that errors in student professional behaviors could influence the fieldwork experience. Both studies emphasized the need for students to self-reflect on behaviors and the education process as suggested in Fidler's (1996) …”
Section: Literature Reviewmentioning
confidence: 99%
“…Fieldwork educators have high professional expectations of their students (Chipchase et al, 2012;Garrett & Schkade, 1995;Jensen & Daniel, 2010;Steward, 2001;Vogel, Grice, Hill, & Moody, 2004). However, the literature on this topic revealed inconsistent definitions of professional behaviors (Breines, 1988;Steward, 2001) yet affirmed that professional behaviors are critical for fieldwork requirements (Holmes & Scaffa, 2009) and success (Gutman, McCreedy, & Heisler, 1998;James & Musselman, 2006).…”
mentioning
confidence: 99%
“…These expert assessors were invited to participate in round one of the Delphi survey via an email link and were sent two reminders over a one month period from the initial invitation. It was predicted that two rounds of the data collection would achieve consensus based on similar work in the practice area …”
Section: Methodsmentioning
confidence: 99%